A interlíngua e o alinhamento léxico-conceitual da base de dados bilíngue REBECA - Di Felippo, Ariani; Silva, Bento Carlos Dias da [UNESP] (My University, 2010)
In the architecture of a natural language processing system based on linguistic knowledge, two types of component are important: the knowledge databases and the processing modules. One of the knowledge databases is the lexical database, which is responsible for providing the lexical unities and its properties to the processing modules. The systems that process two or more languages require bilingual and/or multilingual lexical databases. These databases can be constructed by aligning distinct monolingual databases. In this paper, we present the interlingua and the strategy of aligning the two monolingual databases in REBECA, which only stores concepts from the “wheeled vehicle” domain.

Quando baseados em conhecimento (linguístico), os sistemas que processam língua natural apresentam dois grupos de componentes: as bases de conhecimento e os módulos de processamento. Uma dessas bases de conhecimento é lexical, responsável por fornecer, aos módulos de processamento, as unidades da língua em questão e as suas respectivas propriedades. Os sistemas que processam duas ou mais línguas requerem bases lexicais bilíngues e/ou multilíngues. Tais bases podem ser construídas em função do alinhamento de diferentes bases monolíngues. Neste trabalho, apresentamos a interlíngua e a estratégia de alinhamento utilizadas na construção da base bilíngue REBECA, que engloba conceitos lexicalizados do domínio dos “veículos com rodas”.
The interlingua and the lexical-conceptual alignment in REBECA lexical database
Keywords: Natural Language Processing; REBECA; Lexical database; Interlíngua; Lexicalconceptual alignment; Processamento Automático das Línguas Naturais; REBECA; Bases de conhecimento lexical; Interlíngua; Alinhamento léxico-conceitual